Density functional theory studies on ortho-position adsorption of SO3 at step sites of a CaO surface with SO2 and CO2. (15th February 2022) - Liu, Lu; Shao, Guangcai; Gong, Peng; Wu, Zhiwei; Chu, Jiaming; Hu, Yangang; Wang, Junfeng; Wang, Shuang; Zheng, Chenghang; Gao, Xiang; De Geyter, Nathalie; Morent, Rino
Graphical abstract: Highlights: Steps with O and Ca at the edges are the best termination for SO3 adsorption. Adsorption energy has a remarkable increase at edge sites on step surface. Coordination of O and Ca at edges affect SO3 adsorption. Pre-adsorption of SO3 or SO2 at neighboring sites increases SO3 adsorption energy. SO3 adsorption is more stable than the adsorption of SO2 and CO2 at edge sites. Abstract: With the application of high-sulfur coal and oxy-fuel combustion in power plants, the formation of SO3 in flue gas has strongly enhanced. Hence, the removal of SO3 has received growing attention. Within this context, SO3 sorption using calcium-based sorbents is an interesting approach. In this study, we analyzed the steps on a CaO surface and examined their influence on the adsorption of SO3 molecules using density function theory calculations. The results indicate that steps with O and Ca atoms at the edges are the most stable terminations and also the best terminations for SO3 adsorption. SO3 molecules bind to OCaO sites by SSO3 atoms and weak bonds between Ca and OSO3 are formed. At edge sites, the adsorption energy of SO3, SO2 and CO2 shows a remarkable increase compared to that on a flat surface, whereas it decreases at the top site nearby the edge. The adsorption energy of SO3 is also affected by the OCaO that interacts with SSO3 and the Ca near the OCaO . Interestingly, the SO3 adsorption energy can increase if an SO3, SO2 or CO2 molecule previously adsorbed at a neighboring site. SO3 adsorption is more stable than SO2 and CO2 absorption on step surface and has an advantage in competitive adsorption with SO2 or CO2 . The calculation results thus indicate that the formation of a step surface could be an effective method to enhance SO3 sorption on calcium-based sorbents.